(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
On-farm adaptive Research Methodology was adopted in the year 2023 at two locations to afford a simultaneous trial and transfer/adoption of the maize: cowpea inter-crop farming system. A factorial combination of three seed varieties (i) Ife Brown-NGVU9-1-2 (ii) Ex-Borno (iii) IT90K-82-2 SAMPEA17, three sowing dates (i) 30/08/2023 (ii) 06/09/2023 (iii)13/09/2023 and two geometric arrangements (i) 1:2, (ii) 2:4 of cowpea: maize inter-crop. were combined in a factorial design and allocated in a completely randomized block design to the experimental plots. Ife brown was the first variety to attain 50% flowering within 37 days and 38 days, for Iloffa and Offa respectively. it also produced the tallest cowpea plants (35 and 30 cm) from the two locations. Variety IT90K-82-2-SAMPEA17 recorded the highest nodule count of 59.55 and 55.6. The largest leaf area was recorded from Ex-Borno 127 and 129 Cm2, respectively, from location 1 &2. Late sowing (on 13/09/2023) had a delayed flowering till 44.8 and 43.9 days after sowing. The tallest plants were still produced from sowing on 13/09/2023. Sowing seed on 30/08/2024 produced the largest leaf area (127.8 and 129 cm2). Cowpea sown 1:2 flowered earlier (46.59), while the tallest cowpea (33.7 and 29.15cm) were obtained from sowing in 2:4 spatial arrangements prospectively from location one and two. Sowing 1:2 recorded the higher leaf area of (3.03), while sowing in a 2:4 arrangement gave a higher LAI of (2.60). Ife Brown was observed to be best adapted to the wet Savannah ecology having recorded the most impressive values for the yield indicators when sown on 13 August in a 2:4 spatial arrangement.